Nutlin-3-induced redistribution of chromatin-bound IFI16 in human hepatocellular carcinoma cells in vitro is associated with p53 activation - SHI Xin-li; YANG Jing; MAO Nan; WU Jing-hua; REN Lai-feng; YANG Yuan; YIN Xiao-lin; WEI Lin; LI Ming-yuan; WANG Bao-ning (Acta Pharmacologica Sinica; Vol 36, No 2 (February 2015): Acta Pharmacologica Sinica, 2017)
Aim: Interferon-γ inducible protein 16 (IFI16), a DNA sensor for DNA double-strand break (DSB), is expressed in most human hepatocellular carcinoma cell (HCC) lines. In this study we investigated the re-localization of chromatin-bound IFI16 by Nutlin-3, a DNA damage agent, in HCC cells in vitro, and the potential mechanisms. Methods: Human HCC SMMC-7721 (wild-type TP53), Huh-7 (mutant TP53), Hep3B (null TP53) and normal fetal liver L02 cell lines were examined. DSB damage in HCC cells was detected via γH2AX expression and foci formation assay. The expression of IFI16 and IFNB mRNA was measured using RT-PCR, and subcellular localization and expression of the IFI16 protein were detected using chromatin fractionation, Western blot analysis, and fluorescence microscopy. Results: Treatment of SMMC-7721 cells with Nutlin-3 (10 μmol/L) or etoposide (40 μmol/L) induced significant DSB damage. In SMMC-7721 cells, Nutlin-3 significantly increased the expression levels of IFI16 and IFNB mRNA, and partially redistributed chromatinbound IFI16 protein to the cytoplasm. These effects were blocked by pretreatment with pifithrin-α, a p53 inhibitor. Furthermore, Nutlin-3 did not induce ectopic expression of IFI16 protein in Huh-7 and Hep3B cells. Moreover, the association of IFI16 with chromatin and Nutlin-3-induced changes in localization were not detected in L02 cells. Conclusion: Nutlin-3 regulates the subcellular localization of IFI16 in HCC cells in vitro in a p53-dependent manner.